Beatissimi martyres nazareni. A proposito degli Acta Gallonii e del Libellus precum Harley 7653 - Tomea, Paolo (Analecta Bollandiana, 2010)
This note deals with the term nazareni which is found in one of the prayers in MS Harley 7653 (VIII-IX c.). Its very use as a living term can be linked to its important occurrence in the Acta Gallonii. Since it can be considered an archaism, the prayer may possibly reflect relations between the Irish and Anglo-Saxon world and North Africa and the Near East.